Pediatric window falls: not just a problem for children in high rises. Issue 5 (3rd October 2005) - Vish, N L; Powell, E C; Wiltsek, D; Sheehan, K M
Abstract : Background: Window falls are a frequent cause of injury (15/100 000) among Chicago preschool children. In Boston and New York, public health efforts have successfully decreased window fall injuries. Local data are needed to develop appropriate interventions for Chicago. Objective: To describe the housing characteristics and types of injuries among children who fell from windows treated in a Chicago pediatric trauma center. Methods: Children treated in a pediatric trauma center for injuries related to window falls between 1995 and 2002 were identified retrospectively. We reviewed family demographics, the circumstances of the fall, and types of injuries. Site visits were performed to determine the height and type of building and type of window where the fall took place. Results: The authors reviewed 90 cases; 55 were male. The median age was 2 years. Ninety eight percent of falls were reported to be from the third floor or lower. Site visits (n = 77) showed that 96% of the buildings were four storeys or lower. The median length of hospital stay was two days (range 0–24 days). The most common injuries were head trauma and extremity fractures. Three patients died, and an additional three patients were discharged to rehabilitation centers. Conclusions: Some window falls result in serious injury. In Chicago, most falls were from modest heights (2nd/3rd floor windows) in buildings of four or fewer storeys, rather than from "high rises". Strategies to prevent window falls should be directed to the owners and occupants of this type of housing.